Nano-silica sol reinforced sodium carbonate-stimulated slag regeneration mortar and preparation method thereof

By using nanosilicon sol in sodium carbonate-excited slag material, early C-(N)-A-S-H gel generation is promoted, and the problems of low early strength and slow condensation speed of sodium carbonate-excited slag material are solved, achieving high strength, low shrinkage and good construction performance.

CN117534436BActive Publication Date: 2025-03-18FUJIAN AGRI & FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311531601.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-16
Publication Date
2025-03-18
Estimated Expiration
2043-11-16

AI Technical Summary

Technical Problem

Sodium carbonate-induced slag materials have problems with low strength and slow condensation speed in the early stage, which limits their promotion and application in actual engineering.

Method used

Nanosilicon sol, sodium carbonate and regenerated fine aggregates are used as raw materials, and the reaction of nanosilicon sol with sodium carbonate and slag promotes the generation of early C-(N)-A-S-H gels, inhibits the production of calcium carbonate crystals, thereby improving early strength and coagulation speed.

Benefits of technology

It significantly improves the early strength and condensation speed of the slag regeneration mortar that stimulates sodium carbonate, reduces the shrinkage and cracking properties of the material, and improves the overall strength and bonding properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117534436B_ABST
    Figure CN117534436B_ABST
Patent Text Reader

Abstract

The present invention discloses a nano-silica sol-enhanced sodium carbonate-activated slag regeneration mortar and a preparation method thereof. In the mortar composition of this scheme, sodium carbonate is used as an activator, which has the advantages of widely available raw materials, small corrosiveness and shrinkage cracking, high later strength, low energy consumption and cost, etc.; and the nano-silica sol in the component can well make up for the shortcomings of slow coagulation speed and low early strength caused by sodium carbonate-activated slag, and at the same time can strengthen the interface transition zone of recycled fine aggregate, significantly improve the strength and bonding performance of the mortar; slag and recycled fine aggregate are both solid wastes, which can improve the utilization rate of solid wastes and reduce landfill and land occupation, which is beneficial to environmental governance and protection. On the one hand, the present invention can significantly reduce the emission of greenhouse gases such as carbon dioxide; on the other hand, it can promote the utilization of solid wastes, alleviate the shortage of natural sand and gravel, achieve significant economic, environmental and social benefits, and has broad prospects for promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to nano-silica sol reinforced sodium carbonate excited slag regeneration mortar and a preparation method thereof. Background Art

[0002] The manufacturing process of Portland cement produces a large amount of carbon emissions and is the third largest contributor to the greenhouse effect (accounting for 5-8% of global carbon dioxide emissions). In addition, natural sand and gravel are non-renewable resources. Due to the continuous increase in construction volume, sand and gravel resources are currently in short supply. Therefore, using low-carbon alkali slag cement instead of ordinary Portland cement and using recycled aggregates instead of natural sand and gravel to prepare alkali slag recycled mortar is an important way to achieve green and low-carbon development.

[0003] Alkali slag cement is a hydraulic cementitious material obtained by activating industrial waste slag with alkali activators. Among them, water glass and sodium hydroxide are the most commonly used activators. Although the alkali slag materials activated by them have excellent mechanical properties and durability, they also have problems such as large shrinkage, easy cracking, high cost and energy consumption. Sodium carbonate (Na2CO3), as a widely available, low-cost and green activator, can significantly reduce the shrinkage deformation and cracking of alkali slag materials. However, sodium carbonate-activated slag materials also have problems such as low early strength and slow setting speed. Under normal alkali concentration, its 3-day strength is basically 0 and even difficult to demold, and its 7-day compressive strength is generally 0-20MPa (mainly related to the activity of the slag itself), which limits its promotion and application in actual engineering.

[0004] In order to solve the problems of slow setting speed and low early strength caused by Na2CO3-activated slag, Chinese invention patent CN116283172A discloses an alkali slag cementitious material with Na2CO3 and CaO as activators and its preparation. However, the added CaO will cause the system to produce a large amount of crystalline substances such as calcium carbonate, resulting in a bulky and porous matrix, affecting strength; on the other hand, CaO reacts quickly with water to produce a large amount of hydration heat, causing its setting speed to be too fast and affecting working performance. Therefore, it is necessary to find more ways to solve the shortcomings of Na2CO3-activated slag. In addition, the surface of the recycled fine aggregate is wrapped with old mortar, which has problems such as high water absorption and weak transition zone with the matrix interface, thus resulting in a decrease in strength and increased shrinkage of the material prepared therefrom. To this end, it is essential to seek an effective method to simultaneously solve the problems existing in the application of sodium carbonate-activated slag and recycled aggregate, which is crucial to promote the application of sodium carbonate-activated slag recycled materials.

[0005] Nano-silica sol is a dispersion of nano-SiO2 particles in water. The surface of the particles contains silanol (-SiOH) and hydroxyl (-OH) (see surface structure). Figure 2), has the advantages of high activity, good dispersibility, high adsorption capacity, strong corrosion resistance, etc., and is currently widely used in the fields of coatings, refractory materials, papermaking, textiles, and electronic industries. However, nano-silica sol is less used in alkali-activated systems. The present invention applies nano-silica sol to the alkali-slag regeneration mortar system activated by sodium carbonate, giving full play to its synergistic enhancement effect, which can not only shorten the setting time of the Na2CO3-activated system and improve the early strength; at the same time, a CSH gel coating layer with a low calcium-silicon ratio is formed on the surface of the recycled fine aggregate, further enhancing the interface hardness of the recycled fine aggregate and improving the bonding performance. In summary, the nano-silica sol-enhanced sodium carbonate-activated slag regeneration mortar proposed in the present invention has very high strength and low shrinkage, good technical, economic and environmental advantages, and has broad prospects for promotion and application. Summary of the invention

[0006] In view of this, the purpose of the present invention is to propose a nano-silica sol-reinforced sodium carbonate-activated slag regeneration mortar and its preparation method, which has a simple preparation method, low cost, is green and environmentally friendly and can achieve the recycling of slag and construction solid waste resources.

[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0008] A nano-silica sol reinforced sodium carbonate-stimulated slag regeneration mortar, comprising the following components in percentage by mass:

[0009]

[0010] As a possible implementation manner, further, the nano-silica sol described in this solution includes 30±1wt% SiO2 and Na2O with a solid content of ≤0.3%.

[0011] As a preferred implementation option, preferably, the physical properties of the nano-silica sol described in this scheme are: viscosity: 7mPa.s, density: 1.21-1.29g / cm 3 , particle size: 10~20nm, pH value: 9~10.

[0012] As a possible implementation manner, further, the sodium carbonate described in this solution is in the form of white particles, and its purity is ≥99.8%.

[0013] As a possible implementation mode, further, the slag described in this solution is S95 grade granulated blast furnace slag, which has the following main components in mass percentage:

[0014]

[0015] As a possible implementation method, further, the particle size of the recycled fine aggregate in this solution is 0.15-4.75 mm, the moisture content is 4.5%, the water absorption rate is 7.1%, and the apparent density is 1669.0 kg / m 3 , the bulk density is 1308.4kg / m 3 .

[0016] Based on the above, the present solution also provides a method for preparing the nano-silica sol enhanced sodium carbonate activated slag regeneration mortar, which comprises the following steps:

[0017] (1) Measure each component material according to the preset mass percentage;

[0018] (2) Pour the slag and recycled fine aggregate into a mixer and stir slowly at a speed of 150 r / min for 1 min to obtain a mixed dry material;

[0019] (3) Dissolve sodium carbonate in water in advance and stir for 3 to 5 minutes to fully dissolve it to form a sodium carbonate solution; then pour the sodium carbonate solution into the mixed dry material and stir slowly at 150 r / min for 1 minute, then pour the nano-silica sol into it and stir slowly at 150 r / min for 1 minute, and finally stir quickly at 280 r / min for 1 minute to complete the mortar preparation.

[0020] Based on the above, the present invention also provides an application method of the mortar prepared by the above-mentioned preparation method, which comprises:

[0021] The prepared mortar is poured into a mold, and then removed from the mold after standing for 1 day. The mortar is then placed in a standard curing box with a temperature of 23±2°C and a relative humidity of more than 95% for curing to the specified age.

[0022] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0023] (1) The present invention adopts sodium carbonate as an activator, which has a wide and sufficient source. Compared with the traditional high-energy consumption activator (sodium hydroxide / sodium silicate), the sodium carbonate activator can significantly reduce the shrinkage and cracking of the alkali slag regeneration mortar. In addition, the sodium carbonate activator used has a significant cost advantage and reduces carbon emissions, and has the advantages of low price and green environmental protection.

[0024] (2) The present invention adopts nano-silica sol as one of the raw materials, which has higher surface activity and dispersibility than traditional nano-silica particles. The outermost silicon oxygen bond of nano-silica sol breaks under the action of water to form silanol (-SiOH), which together with alkali metal ions forms a stable diffuse double layer ( Figure 3 ), which makes it have excellent surface activity. In addition, nano silica sol has ζ (Zeta) potential ( Figure 3), Brownian motion and solvent barrier effect, making the reaction more uniform and further improving the overall strength of the material.

[0025] (3) The nano-silica sol, sodium carbonate and recycled fine aggregate used in the present invention have a synergistic effect. The surface silanol (-SiOH) of the nano-silica sol can be preferentially oxidized to CO3 in sodium carbonate. 2- and Ca dissolved in slag 2+ The reaction promotes the early generation of C-(N)-ASH gel and inhibits the generation of calcium carbonate crystals, so that the matrix forms a denser spatial network structure, thereby shortening the setting time and improving the early strength. At the same time, the nano-silica sol reacts with the Ca(OH)2 in the old mortar on the surface of the recycled fine aggregate to form a CSH gel coating with a low calcium-silicon ratio, which enhances the interfacial adhesion between the recycled fine aggregate and the slurry, thereby improving the strength of the recycled mortar.

[0026] (4) The slag used in the scheme of the present invention is industrial solid waste, and the recycled fine aggregate is also construction solid waste, which can achieve dual solid waste utilization effects, reduce the emission of greenhouse gases such as carbon dioxide, alleviate the shortage of natural sand and gravel, and reduce landfill land and costs, with good economic and environmental benefits.

[0027] In summary, the scheme of the present invention adopts nano-silica sol, sodium carbonate and recycled fine aggregate to produce alkali slag regenerated mortar, which has a good synergistic enhancement effect, moderate setting speed, good workability, high strength, excellent durability, simple preparation, convenient construction, low carbon and environmental protection, and low cost, and has good application value and promotion prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 It is a characterization diagram of the particle size distribution of the slag used in the scheme of the present invention;

[0030] Figure 2 This is a schematic diagram of the surface structure of nano silica sol particles of the present invention;

[0031] Figure 3 This is a schematic diagram of the double electric layer structure and zeta potential of the nano-silica sol of the present invention;

[0032] Figure 4 It is a comparative schematic diagram of the setting time of the cementitious material of the scheme of the present invention;

[0033] Figure 5 Schematic diagram of the comparison of the setting time of the mortar according to the present invention;

[0034] Figure 6 Schematic diagram of the comparison of mortar fluidity of the present invention;

[0035] Figure 7 This is a comparison chart of the flexural strength of the mortar of the present invention at 3d, 7d, 14d, and 28d;

[0036] Figure 8 It is a comparison chart of the compressive strength of the mortar of the present invention at 3d, 7d, 14d and 28d;

[0037] Fig. 9 This is a comparison chart of the mechanical strength folding-compression ratio of the mortar after the samples are made according to the scheme of the present invention;

[0038] Fig.10 This is a comparison chart of heat release rates of the gelling materials of the present invention;

[0039] Fig.11 This is a comparison diagram of the cumulative heat release of the gelling material of the present invention;

[0040] Fig.12 This is a comparison chart of the 3D thermogravimetric loss of the gelling material of the present invention;

[0041] Fig.13 This is a comparison diagram of the 3d thermogravimetric loss differential curve of the gelling material of the present invention;

[0042] Fig.14 It is a comparison diagram of the micromorphology-energy spectrum scanning diagram of the mortar of the embodiment of the scheme of the present invention and the comparative example after curing for 28 days, wherein Figures a1, b1, c1, and d1 are respectively the micromorphology characterization diagrams of the comparative example and embodiments 1, 2, and 3 at 1000 times, Figures a2, b2, c2, and d2 are respectively the micromorphology characterization diagrams of the comparative example and embodiments 1, 2, and 3 at 20000 times, and Figures a3, a4, c3, and c4 are respectively the Si element energy spectrum surface scanning characterization diagrams and Si element proportion characterization diagrams of the comparative example and embodiment 2. DETAILED DESCRIPTION

[0043] The present invention will be further described in detail below in conjunction with the accompanying drawings and examples. It is particularly noted that the following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention. Similarly, the following examples are only partial embodiments of the present invention rather than all embodiments, and all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.

[0044] The present embodiment provides a nano-silica sol enhanced sodium carbonate-activated slag regeneration mortar and a preparation and application method thereof. The nano-silica sol enhanced sodium carbonate-activated slag regeneration mortar is composed of nano-silica sol, sodium carbonate, slag, recycled fine aggregate and water. The mass percentage of each component ranges from 1.2% to 2.4% of nano-silica sol, 2.3% of sodium carbonate, 21.5% to 21.9% of slag, 64.7% of recycled fine aggregate, and 9.1% to 9.9% of water. The sum of the mass percentages of each component is 100%.

[0045] In terms of preparation and application, the mortar of this scheme includes the following steps:

[0046] (1) Measure the components according to the above ratios;

[0047] (2) Pour the slag and recycled fine aggregate into a mixer and stir slowly at a speed of 150 r / min for 1 min to obtain a mixed dry material;

[0048] (3) Dissolve sodium carbonate in water in advance and stir for 3 to 5 minutes to fully dissolve it to form a sodium carbonate solution; then pour the sodium carbonate solution into the mixed dry material and stir slowly at a speed of 150 r / min for 1 minute, then pour the nano-silica sol into it and stir slowly at a speed of 150 r / min for 1 minute, and finally stir quickly at a speed of 280 r / min for 1 minute to obtain mortar, which is then poured into a mold;

[0049] (4) After standing for 1 day, remove the mold and then place it in a standard curing box with a temperature of 23±2℃ and a relative humidity of more than 95% for curing to the specified age.

[0050] The following is a further technical description of the present invention in combination with a number of embodiments and comparative examples:

[0051] Example 1

[0052] The present embodiment provides a nano-silica sol enhanced sodium carbonate stimulated slag regeneration mortar, which is mainly composed of nano-silica sol, sodium carbonate, slag, recycled fine aggregate and water, and the mass percentage of each component is: nano-silica sol 1.2%, sodium carbonate 2.3%, slag 21.9%, recycled fine aggregate 64.7%, water 9.9%, and the sum of the mass percentages of each component is 100%.

[0053] Accordingly, in terms of the preparation and application of mortar, the present embodiment includes the following steps:

[0054] (1) Measure the components according to the above ratios;

[0055] (2) Pour the slag and recycled fine aggregate into a mixer and stir slowly at a speed of 150 r / min for 1 min to obtain a mixed dry material;

[0056] (3) Dissolve sodium carbonate in water in advance and stir for 3 to 5 minutes to fully dissolve it to form a sodium carbonate solution; then pour the sodium carbonate solution into the mixed dry material and stir slowly at a speed of 150 r / min for 1 minute, then pour the nano-silica sol into it and stir slowly at a speed of 150 r / min for 1 minute, and finally stir quickly at a speed of 280 r / min for 1 minute to obtain mortar, which is then poured into a mold;

[0057] (4) After standing for 1 day, remove the mold and then place it in a standard curing box with a temperature of 23±2℃ and a relative humidity of more than 95% for curing to the specified age.

[0058] Example 2

[0059] The present embodiment provides a nano-silica sol enhanced sodium carbonate stimulated slag regeneration mortar, which is mainly composed of nano-silica sol, sodium carbonate, slag, recycled fine aggregate and water, and the mass percentage of each component is: 1.8% of nano-silica sol, 2.3% of sodium carbonate, 21.7% of slag, 64.7% of recycled fine aggregate, and 9.5% of water, and the sum of the mass percentages of each component is 100%.

[0060] The preparation and application methods of the nano-silica sol-reinforced sodium carbonate-stimulated slag regeneration mortar in this embodiment are the same as those in Example 1 and will not be described in detail here.

[0061] Example 3

[0062] The present embodiment provides a nano-silica sol enhanced sodium carbonate stimulated slag regeneration mortar, which is mainly composed of nano-silica sol, sodium carbonate, slag, recycled fine aggregate and water, and the mass percentage of each component is: nano-silica sol 2.4%, sodium carbonate 2.3%, slag 21.5%, recycled fine aggregate 64.7%, water 9.1%, and the sum of the mass percentages of each component is 100%.

[0063] The preparation and application methods of the nano-silica sol-reinforced sodium carbonate-stimulated slag regeneration mortar in this embodiment are the same as those in Example 1 and will not be described in detail here.

[0064] Comparative Example

[0065] This comparative example is substantially the same as Example 1, except that nano-silica sol is not added as a component in this comparative example.

[0066] This comparative example provides a sodium carbonate-activated slag regeneration mortar, which is mainly composed of sodium carbonate, slag, recycled fine aggregate and water. The mass percentage of each component is: 2.3% sodium carbonate, 22.2% slag, 64.7% recycled fine aggregate, 10.8% water, and the sum of the mass percentages of each component is 100%.

[0067] Accordingly, in terms of the preparation and application of mortar, the present embodiment includes the following steps:

[0068] (1) Measure the components according to the above ratios;

[0069] (2) Pour the slag and recycled fine aggregate into a mixer and stir slowly at a speed of 150 r / min for 1 min to obtain a mixed dry material;

[0070] (3) Dissolve sodium carbonate in water in advance and stir for 3 to 5 minutes to fully dissolve it to form a sodium carbonate solution; then pour the sodium carbonate solution into the mixed dry material and stir slowly at a speed of 150 r / min for 1 minute, and then stir quickly at a speed of 280 r / min for 1 minute to obtain mortar, which is then poured into a mold;

[0071] (4) Remove the mold after standing for 3 days (if the mold cannot be removed successfully 3 days ago), and then place it in a standard curing box with a temperature of 23±2℃ and a relative humidity of more than 95% for curing to the specified age.

[0072] In order to avoid more error factors in the comparative test results due to different raw materials, the characteristics of the raw materials used in the above embodiments or comparative examples are as follows:

[0073] The slag has the main chemical components shown in Table 1 below (the remainder is other trace components and ignition loss):

[0074] Table 1 Chemical composition of slag

[0075]

[0076] The particle size distribution of the slag is characterized by Figure 1 shown.

[0077] Sodium carbonate is white granular, with a purity of ≥99.8%;

[0078] The particle size of recycled fine aggregate is 0.15-4.75 mm, the moisture content is 4.5%, the water absorption rate is 7.1%, and the apparent density is 1669.0 kg / m 3 , the bulk density is 1308.4kg / m 3

[0079] The nano-silica sol used in Examples 1, 2 and 3 includes 30±1wt% SiO2 and Na2O with a solid content of ≤0.3%. The physical properties of the nano-silica sol are as follows: viscosity: 7mPa.s, density: 1.21-1.29g / cm 3 , particle size: 10-20nm, pH value: 9-10. The schematic diagram of the surface structure of nano-silica sol particles is as follows Figure 2 As shown in the figure, the double electric layer structure and zeta potential of nano-silica sol are as follows Figure 3 shown.

[0080] Comparative test

[0081] In order to facilitate the performance testing and comparison of the mortars prepared in the embodiments and comparative examples and the products cast therefrom, this scheme mainly compares the following tests, and the specific items and parameters are as follows:

[0082] (1) Setting time test: The setting time test of cementitious materials shall be carried out in accordance with the "Test Methods for Water Consistency, Setting Time and Stability of Cement at Standard Consistency" (GB / T 1346-2011), and the testing instrument shall be the NLD-3 Vicat instrument; the setting time test of mortar shall be carried out in accordance with the "Standard Test Methods for Basic Properties of Building Mortar" (JGJ / T 70-2009), and the testing instrument shall be the ZKS-100 Mortar Setting Time Meter.

[0083] (2) Mortar fluidity test: refer to the "Method for Determination of Fluidity of Cement Mortar" (GB / T 2419-2005), and the test instrument is the NLD-3 cement mortar fluidity tester.

[0084] (3) Mortar mechanical properties test: refer to the "Test Method for Strength of Cement Mortar" (GB / T 17671-2021). The flexural strength is tested using a rectangular specimen with a size of 40 mm × 40 mm × 160 mm. After the flexural strength test, the two halves of the specimen are taken out for compressive strength test. The test ages are 3d, 7d, 14d, and 28d, respectively. The tests are carried out using a YAW-300C fully automatic flexural and compressive testing machine.

[0085] (4) Hydration heat test: This test was conducted using a TAM Air isothermal calorimeter (TA Instruments, USA). The isothermal calorimeter has an operating temperature range of 5 to 90°C and is equipped with a circulating air constant temperature bath with an accuracy of ±0.02°C. The test was conducted under isothermal conditions (25±0.1°C).

[0086] (5) Thermogravimetric test: The test was performed using a synchronous thermal analyzer (STA449F3) from Netzsch, Germany. The test conditions were: the test temperature range was from room temperature to 1000°C, the heating rate was 10°C / min, and the atmosphere was nitrogen.

[0087] (6) Scanning electron microscope test (microstructure / energy spectrum scanning): This test was conducted using a German ZEISS Gemini300 field emission scanning electron microscope. The accelerating voltage was 3 kV when the morphology was photographed. An Oxford Quorum SC7620 sputtering coater was used for gold spraying, and the gold spraying target was platinum.

[0088] Comparison of test results

[0089] The mortars or cast products thereof prepared in Examples 1, 2, 3 and the comparative example were subjected to the test items of the aforementioned comparative tests (1) to (6), and the results obtained were as follows:

[0090] (1) Combination Figure 4 , Figure 5 The comparison of the setting time of gel material and mortar shows that with the increase of the amount of nano-silica sol, the initial setting and final setting time of the gel material gradually shortens ( Figure 4 ), the mortar setting time is gradually shortened ( Figure 5 ). Within the scope of this test, the initial setting time of cementitious materials can be shortened by about 4 to 22 times, and the final setting time can be shortened by about 1 to 13 times, which can meet the setting time standard of ordinary Portland cement and can become an excellent substitute for ordinary Portland cement; the setting time of mortar can be shortened by 3 to 5 times, which can meet the construction requirements. It can be seen that the addition of nano-silica sol promotes slag hydration and solves the problem of slow setting speed of slag stimulated by sodium carbonate.

[0091] (2) Combination Figure 6 The comparison of mortar fluidity shows that as the amount of nano-silica sol increases, the mortar fluidity shows a trend of gradually decreasing. This is mainly because nano-silica sol has a large specific surface area, strong adsorption and a certain viscosity. It will form flocculation in alkaline solution, which increases the consistency of the fresh slurry and reduces the rheological properties. However, the overall rheological properties of each embodiment do not change much, and the expansion can reach more than 150mm, which can meet the construction requirements.

[0092] (3) Combination Figure 7 , Figure 8 The comparison of mechanical properties of mortar shows that the control specimen has no mechanical strength in the early 3d, and after adding nano-silica sol, the mechanical properties develop rapidly in the early stage, and the 3d flexural strength ( Figure 7 ) and compressive strength ( Figure 8 ) can reach up to 6.44MPa and 30.5MPa (Example 2), respectively. Compared with the comparative example, the 7d, 14d, and 28d flexural strength of Example 2 are increased by 87.6%, 50.6%, and 24.7%, respectively, and the compressive strength is increased by 98.9%, 61.0%, and 19.9%, respectively. The early mechanical properties are improved more significantly, which is mainly due to the fact that the nano-silica sol particles can be used in preference to CO3 2- and Ca dissolved from slag 2+ reaction and provide more nucleation sites, thus more hydration products can be generated at an early stage (see thermogravimetric analysis, Fig.10 , Fig.11 ). With the increase of nano-silica sol dosage, the mechanical strength shows a trend of increasing first and then decreasing. This is mainly because excessive dosage is prone to agglomeration, which reduces the homogeneity of the material and thus affects the strength. Fig. 9), the folding-compression ratio of the comparative example and the example gradually decreases with the increase of age. This is mainly because the later increase of compressive strength is much higher than the flexural strength, which is in line with the basic development law of cement-based materials. The folding-compression ratio can reflect the brittleness of the material (related to the bonding strength between the slurry and the aggregate and the generation and development rate of matrix cracks). The smaller the folding-compression ratio, the greater the brittleness. The folding-compression ratio of Example 1 is the largest, indicating that at the appropriate dosage, nano-silica sol can reduce the brittleness of the material. The main reason is that the nano-silica sol particles react with the Ca(OH)2 in the old mortar on the surface of the recycled fine aggregate to form a CSH gel coating with a low calcium-silicon ratio, which enhances the bonding strength between the recycled aggregate and the slurry while reducing the probability and development rate of matrix cracks.

[0093] (4) Combination Fig.10 , Fig.11 The comparison of hydration heat shows that as the amount of nano-silica sol increases, the heat release rate of the gelling material increases ( Fig.10 ), the dissolution peak value in the initial pre-induction period of about 6 hours increases, and the time of the induction period (the second exothermic peak) gradually shortens, from 151.3 hours in the comparative example to 73.8 hours, 27.1 hours, and 23.1 hours, respectively. The change pattern corresponds to the setting time. This is mainly because the cementitious material has to go through three processes under the action of sodium carbonate alone, from the dissolution of slag to the formation of monoclinic sodium calcium calcium stone and zeolite, to the conversion of monoclinic sodium calcium calcium stone to the formation of CaCO3 and hydrotalcite, and finally to the precipitation of CASH gel, which prolongs the induction period of 4 to 6 days. The addition of nano-silica sol can take precedence over CO3 2- and Ca dissolved from slag 2+ The reaction forms CASH gel in advance and provides more nucleation sites to further promote slag hydration and increase the reaction rate. The cumulative heat release of Example 2 is the highest (consistent with the thermogravimetric analysis results), while that of Example 3 is the lowest ( Fig.11 ), mainly due to the large dosage. Although the heat release rate is the fastest, the uneven dispersion caused by it will affect the formation of hydration products in the later stage, thereby reducing the overall heat release.

[0094] (5) Combination Fig.12 , Fig.13 The comparison of thermogravimetric analysis shows that thermogravimetric analysis mainly determines the amount of hydration products by decomposing the different forms of free water in the hydration products at high temperature. Compared with the comparative example, the addition of nano-silica sol makes the total mass loss of 3d in each example ( Fig.12 ) and C-(N)-ASH gels increased in water loss (50-200℃). Fig.13 ), indicating that the amount of overall hydration products and C-(N)-ASH gel generated in the early stage increased, among which the hydration products of Example 2 were the largest, corresponding to the cumulative heat release of its mechanical strength and hydration heat.

[0095] (6) Combination Fig.14 The comparison of microscopic morphology and energy spectrum scanning shows that more cracks appear in the comparative example ( Fig.14 a1 and a2), and the crack width is large, and the proportion of Si element (the higher the purple brightness, the denser the Si element) inside the mortar is low ( Fig.14 In a3 and a4), the generated C-(N)-ASH gel is less and the surface is loose and fragile, which is also the reason for its poor mechanical strength. After adding nano-silica sol, the proportion of Si element in the mortar increases, and the amount of C-(N)-ASH gel generated increases and is more widely distributed ( Fig.14 In b2, c2, and d2), the cracks are significantly reduced, the matrix is ​​more compact, and the silica particles react with the Ca(OH)2 in the old mortar on the surface of the recycled aggregate to form CSH gel ( Fig.14 In d2), the interfacial bonding strength is improved, thereby significantly improving its mechanical properties. In addition, the unreacted nano-silica sol particles can penetrate into the pores, dehydrate and polymerize to form a gel to produce a micro-filling effect, which can further optimize the pore structure and improve the mechanical properties and durability.

[0096] The above descriptions are only some embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Any equivalent device or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A nano-silica sol reinforced sodium carbonate-activated slag regeneration mortar, characterized in that: It is composed of the following components in percentage by mass: Nano silica sol 1.2~2.4% Sodium carbonate 2.3% Slag 21.5%~21.9% Recycled fine aggregate 64.7% Water 9.1%~9.9%; The nano-silica sol comprises 30±1 wt% SiO2 and Na2O with a solid content of ≤0.3%; the physical performance indicators of the nano-silica sol are: viscosity: 7 mPa.s, density: 1.21~1.29 g / cm 3 , particle size: 10~20 nm, pH value: 9~10; the sodium carbonate is white granular and its purity is ≥99.8%.

2. The nano-silica sol reinforced sodium carbonate activated slag regeneration mortar according to claim 1, characterized in that: The slag is S95 grade granulated blast furnace slag, which has the following main components in mass percentage: CaO 41.53% SiO226.02% Al2O315.51% MgO 8.88% SO31.04% TiO20.69% Na2O 0.58% K2O 0.25% Fe2O33.61% MnO 1.26%.

3. The nano-silica sol reinforced sodium carbonate-stimulated slag regeneration mortar according to claim 1, characterized in that: The particle size of the recycled fine aggregate is 0.15-4.75 mm, the moisture content is 4.5%, the water absorption rate is 7.1%, and the apparent density is 1669.0 kg / m 3 , the bulk density is 1308.4 kg / m 3 .

4. The method for preparing the nano-silica sol-reinforced sodium carbonate-stimulated slag regeneration mortar according to any one of claims 1 to 3, characterized in that: It includes the following steps: (1) Measure each component material according to the preset mass percentage; (2) Pour the slag and recycled fine aggregate into a mixer and stir slowly at 150 r / min for 1 min to obtain a mixed dry material; (3) Dissolve sodium carbonate in water in advance and stir for 3 to 5 minutes to fully dissolve it to form a sodium carbonate solution; Then pour the sodium carbonate solution into the mixed dry material and stir slowly at 150 r / min for 1 min, then pour the nano-silica sol into it and stir slowly at 150 r / min for 1 min, and finally stir quickly at 280 r / min for 1 min to complete the mortar preparation.

5. The application method of the mortar obtained by the preparation method according to claim 4 is characterized in that: It includes: The prepared mortar is cast into a mold, then removed from the mold after standing for 1 day, and then placed in a standard curing box with a temperature of 23 ± 2°C and a relative humidity of more than 95% for curing to the specified age.

Citation Information

Patent Citations

  • Low-carbon high-strength micro-expansion grouting material and preparation method thereof

    CN113387664A

  • Slag-based high-strength grouting agent

    JP1997165576A